Locus/Chromosome Aberrations in Intraductal Papillary Mucinous Neoplasms Analyzed by Fluorescence In Situ Hybridization. (April 2015) - Miyabe, Katsuyuki; Hori, Yasuki; Nakazawa, Takahiro; Hayashi, Kazuki; Naitoh, Itaru; Shimizu, Shuya; Kondo, Hiromu; Nishi, Yuji; Yoshida, Michihiro; Umemura, Shuichiro; Kato, Akihisa; Ohara, Hirotaka; et al.
Abstract : Locus and chromosome abnormalities have not been well clarified in intraductal papillary mucinous neoplasms (IPMNs). The aim of this study was to retrospectively examine these abnormalities using fluorescence in situ hybridization. IPMNs (n=28) were histopathologically classified into noninvasive IPMN (n=17) and IPMN with an associated invasive carcinoma (invasive IPMN, n=11) groups. Noninvasive IPMNs possessed non-neoplastic and noninvasive spots in their tissues, and invasive IPMN cases possessed non-neoplastic, noninvasive, and invasive spots. Non-neoplastic (n=28), noninvasive (n=28), and invasive (n=11) spots were then analyzed for aneuploidy of chromosomes 3, 6, 7, 8, 17, and 18 and deletions of p16 and p53 loci. Polysomy 6 and p16 deletion were significantly more frequent in noninvasive than in non-neoplastic spots. Polysomy 7, polysomy 18, p16 deletion, and p53 deletion were significantly more frequent in invasive than in noninvasive spots. Detection of polysomy 7 and p53 deletion gave a high diagnostic accuracy for invasive IPMN (sensitivity, 90.9%; specificity, 94.1%; and accuracy, 92.5%). Our study suggests that: (1) polysomy 6 and p16 deletion may contribute to adenomatous change of IPMN; (2) polysomy 7, polysomy 18, p16 deletion, and p53 deletion play roles in malignant transformation of noninvasive IPMN; and (3) polysomy 7 and p53 deletion may be excellent diagnostic markers for invasive IPMN. Abstract : Supplemental Digital Content is available in the text.